Clinical Outcomes of Self-Expandable Metal Stents for Malignant Rectal Obstruction. Issue 1 (January 2018) - Lee, Hyun Jung; Hong, Sung Pil; Cheon, Jae Hee; Kim, Tae Il; Kim, Won Ho; Park, Soo Jung
Abstract : BACKGROUND: Self-expandable metal stents are widely used to treat malignant colorectal obstruction. However, data on clinical outcomes of stent placement for rectal obstruction specifically are lacking. OBJECTIVE: We aimed to investigate the clinical outcomes of self-expandable metal stents in malignant rectal obstruction in comparison with those in left colonic obstruction and to identify factors associated with clinical failure and complication. DESIGN: This was a retrospective study. SETTINGS: The study was conducted at a tertiary care center. PATIENTS: Between January 2005 and December 2013, medical charts of patients who underwent stent placement for malignant rectal or left colonic obstruction were reviewed retrospectively. INTERVENTION: Study intervention included self-expandable metal stent placement. MAIN OUTCOME MEASURES: Technical success, clinical success, and complications were measured. RESULTS: Technical success rates for the 2 study groups (rectum vs left colon, 93.5% vs 93.1%; p = 0.86) did not differ significantly; however, the clinical success rate was lower in patients with rectal obstruction (85.4% vs 92.1%; p = 0.02). In addition, the complication rate was higher in patients with rectal obstruction (37.4% vs 25.1%; p = 0.01). Patients with rectal obstruction showed higher rates of obstruction because of extracolonic malignancy (33.8% vs 15.8%; p < 0.001) and stent use for palliation (78.6% vs 56.3%; p < 0.001). Multivariate analysis indicated obstruction attributed to extracolonic malignancy and covered stent usage to be independent risk factors for clinical failure. Factors predictive of complications in the palliative group were total obstruction, obstruction because of extracolonic malignancy, and covered stent usage. LIMITATIONS: This was a retrospective, single-center study. CONCLUSIONS: The efficacy and safety of stent placement for malignant rectal obstruction were comparable with those for left colonic obstruction. However, obstruction attributed to extracolonic malignancy, use of covered stents, and total obstruction negatively impacted clinical outcomes of self-expandable metal stent placement and must be considered by endoscopists. SeeVideo Abstract athttp://links.lww.com/DCR/A417 .